Juvenile Justice as a System: Law Enforcement to Rehabilitation - Coffey A. R. (Englewood Cliffs, N. J. Prentice-Hall, Inc., 1974)
This book is an introduction to the American system of juvenile justice. With emphasis on the system, the relationships among police, juvenile court, juvenile probation, correctional institutions, and juvenile parole provide the primary focus of this introduction.
Keywords: 34 .